Rapid material estimation for reinforced concrete construction utilizing a parametric tool for Aceh's postdisaster case - Atthaillah, .; Saputra, E.; Fahrizal, E.; Bambang, Karsono; Fithri, C.A. (IOP Publishing, 2020)
This paper offered a new open-source parametric tool for reinforced-concrete construction estimation for post-disaster based on Aceh's case. The tool aimed at introducing and providing an innovative solution of estimation for building materials more dynamically and rapidly. The tool was initiated by the fact that the delay of relief shelter deployment in 2004 post-tsunami in Aceh of Indonesia was caused by the inability to provide a rapid calculation for building materials as a result of a massive request [1]. Further, the reinforcedconcrete constructions had become a positive preference by the Acehnese [2]. In order to offer a new tool for rapid and dynamic estimation specifically for reinforced-concrete construction, the authors utilized visual scripting of Grasshopper with GHPython extension for optimization of the proposed tool. The tool introduced in this paper was the improvement of previously explored workflows by the authors and ended up with an innovative tool for modeling, visualizing, and estimating. Furthermore, the tool enhanced users' experiences to construct a workflow based on users' specific logic. The tool allowed alterations in the design without comprising time for estimation. In this way, the specific need of the victims in post-disaster was accommodated without obstruction to an estimation of building materials, thus, improved quality and management of the relief shelters for a post-disaster.